Single phase multilevel inverter to improve total harmonic distortion - Md Azuan, Alias (2009)
Nowadays there are many types of single phase multilevel converter. Cascaded multilevel inverter is one of the topologies that meet the specifications in order to get the output waveform similar to sinusoidal waveform. In this project, it has been approved to develop one of the multilevel converters which is using cascaded multilevel inverter to get the output waveform similar to sinusoidal waveform. The primary benefit using this type of converter is to drive an ac load with only using low DC power supply. It is been useful because DC supply proven to be the easiest way to control an AC systems. Basically, this type of converter widely used in motor drives systems, HVDC transmissions, solar systems, Uninterruptable Power Supply (UPS). Cascaded multilevel inverter is a device with high efficiency, stability, and easy to handle. In order to design this project, the main switch must be choosing correctly. MOSFETs 1RF740 are used in this project because of high frequency switching and high voltage rating. Switching in this converter will be the main part which is controlled by microcontroller because of high frequency switching. Microcontroller will provide accurate value of the switching angle to each driver of the switch. The microcontroller also used to make the systems works as planned. Because of this converter using 8 pairs of switch, it takes 2 PlC to control the entire switching angle with different duty cycle. Because IRF 740 needs at least 1OV in order to operate (Vg), the driver needs to install between the PlC and IRF 740 to amplify the signal from microcontroller. Therefore, the IR 2109 is choosing for the driver of this converter.